Energy management of hybrid electric vehicles with battery aging considerations: Wheel loader case study. (May 2021) - Shafikhani, Iman; Å slund, Jan
Abstract: This paper presents a multi-objective energy management strategy for hybrid electric vehicles. It aims at reducing fuel consumption and minimizing battery wear simultaneously while fulfilling system's constraints. A control-oriented differential model is considered to account for battery aging effects, and an algorithm is developed to identify its parameters. The energy management is formulated as an optimal control problem and is solved by Pontryagin's minimum principle. The controller is then implemented for a hybrid electric wheel loader to demonstrate its effectiveness. In short-term simulations for four drive cycles, behavior of the vehicle is compared to the case where the energy management policy does not encompass battery wear minimization. Long-term simulations suggest that there is a huge potential in extending battery life while the price to pay is a negligible increase in fuel consumption. It is observed that the proposed methodology works best for nonaggressive drive cycles. Highlights: A differential battery capacity fade model is used for energy management analysis. A two-step algorithm is proposed to identify the aging model parameters. Battery lifetime can be notably improved for negligible increase in fuel consumption. The battery-friendly strategy performs best for nonaggressive drive cycles.